Han Feizi, The Art of Statecraft in Early China (Vol.2) : A Bilingual Edition - Petersen, Jens Østergaard,; Pines, Yuri, (Human Rights and Humanitarian Law E-Books Online, Collection 2025., 2025)
Volume 2 of a 2-volume set: This annotated translation of Han Feizi introduces one of China's most controversial political texts. Generations of Chinese literati have deplored Han Feizi 's cynical assault on moralising discourse, blatant authoritarianism, and gleeful derision of fellow intellectuals. Yet many were attracted to the text's practical advice, especially its advocacy of reliance on impartial standards rather than on the personal qualities of the leaders (who may be dupes, selfish, or both). And many more admired the text's incisiveness, wit, humour, and realistic approach to politics. The new translation makes the text's political philosophy and its literary gems accessible to the interested readers.